Asocio de Arachis Pintoi con Gramineas: una opción para el uso sostenible de la tierra en sistemas ganaderos - Pezo, Danilo (Universidad de Costa Rica, 2013)
Arachis pintoi / grass mixtures: an alternative for sustainable land use in livestock systems. Arachis pintoi is a tropical legume adapted to medium/low fertility acid soils, grows well at elevations between 0 to 1800 m.a.s.l, prefers rainfall ranging from 2000 to 3500 mm, distribuited at least in 8 months. A. pintoi is shade tolerant, compatible with many grasses, and has several morphological and physiological mechanisms which allow it to persist, even under intense defoliation. Due to its high nutritional value and ability to fix athmospheric N2, A. pintoi not only contributes to improve diet quality in grass/legume mixtures, but also to increase growth rate and CP content of the associated grass. Moreover, in this type of pastures nutrient cycling efficiency is enhanced, and many physycal, fertility and biological soil parameters associated to sustainability tend to be improved. Animal production parameters obtained for grass/A. pintoi mixtures are promising. Criollo x Jersey crossbred cows fed only Arachis / african stargrass pastures, managed with a stocking rate (SR) of 2.4 cows- /ha produced 10.8 kg milk/day, whereas the corresponding milk yield for african stargrass (Cynodon nlemfuensis) pastures, fertilized with 100 kg N/ha/ year was only 9.5 kg/ day. Regarding to beef production, the highest yields (937 kg LWG/ha/year) were obtained in the humid tropics, when A. pintoi/B. brizantha pastures were managed with a SR of 6.0 steers/ha.